Skrining Perkembangan Anak melalui KPSP di Posyandu Seruni 8 di Wilayah Puskesmas Tondano Kota Pekalongan - Ida Baroroh; Putri Andanawarih (LPPM Akbid Harapan Ibu Pekalongan, 2026)
Child development can be disrupted and pose a risk of long-term problems such as speech disorders, motor delays, or behavioral disorders. Therefore, a health service capable of conducting regular monitoring and providing education to parents is needed to ensure children's nutritional and stimulation needs are met. Integrated Health Posts (Posyandu) serve as community-based health service providers that help detect growth and developmental abnormalities early and provide early intervention before more serious disorders occur. To address this, the Indonesian Ministry of Health introduced the Pre-Screening Development Questionnaire (KPSP) as a simple tool for health workers and Posyandu cadres. Recognizing the importance of child development screening, the team conducted a community service project titled